The Effects on Social Media Interactions and Emotional Intelligence on Self-Control - Nisa, Isti Hhoirun; Sugiharto, DYP; Ahmadi, Farid (Jurnal Bimbingan Konseling, 2023)
Students are known to have less self-control in interacting with others. It is indicated by several excessive emotional expressions, such as mocking, insulting, and even fighting, so there is a need for a school counseling to improve students’ self-control. This study aimed at exploring the effects of social media interactions and emotional intelligence on the self-control of students at SMP Negeri 1 Sribhawono. It used a correlational design and involved 59 students whose data were collected using the scales of social media interactions, emotional intelligence, and self-control. Findings revealed (1) There was a positive and significant effect of social media on students’ control (β=0,427, p < 0,01), (2) There was a positive and significant effect of emotional intelligence and self-control (β=0,443, p < 0,01), and (3) social media interactions and emotional intelligence simultaneously affected students’ self-control (R = 0,824, p < 0,01). Based on the findings, it is concluded that social media interactions and emotional intelligence can improve the self-control of students at SMP Negeri 1 Sribhawono.